ETHICS, SOCIAL RESPONSIBILITY AND CORRUPTION AS RISK FACTORS - GRIBINCEA, Alexandru (Annals of Spiru Haret University. Economic Series, 2017)
The financial risk characterises the variability of net profit, subject to the financial structure of the insurance. The capital of the insurance company has two elements (the equity and the borrowed one) that differ fundamentally in the cost they generate. If the company uses loans, it will bear systematically the related financial expenses, too. Through its size and cost, indebtedness leads to the variation and changes the size of financial risk. Resorting to the debt is justified through the high remuneration of equity in relation to borrowed capital, thus increasing the financial return.